Analysing influential factors in university selection using Fuzzy TOPSIS / Nurul Athilah Azaman ... [et al.] - Azaman, Nurul Athilah; Bidin, Jasmani; Sharif, Noorzila; Ku Akil, Ku Azlina (UiTM Cawangan Perlis, 2023)
Students must carefully choose their university because it will affect their motivation for studying, dedication, and engagement with the university. Normally, students will consider some factors that influence their choice of the university. Therefore, this study aims to determine the most important factor that influences students' choice of university. The study also analyses the preferable university either IPTA or IPTS. Besides, the study is conducted to rank the six variables: the influence of family, the influence of friends, the university's image, the university's environment, suitability with personality and interest, and financial support. The data was collected by distributing questionnaires to 30 experts which are teachers and counsellors. They are required to evaluate the issues in this study using linguistic variables ranging from "unaffected" to "very affected". The data was analysed using Fuzzy TOPSIS. The finding shows that the most influential factor in deciding the university selection is the suitability with personality and interest with a closeness coefficient of 0.4869. The influence of friends is the least important in university selection with a closeness coefficient of 0.4713. This study's findings might benefit communities such as students, parents, and teachers. Universities may also benefit from it because they need to attract more students to expand their market.